Patriotic elaborations : essays in practical philosophy - Blattberg, Charles (McGill-Queen's University Press, 2009)
How might we mend the world? Charles Blattberg suggests a "new patriotism," one that reconciles conflict through a form of dialogue that prioritizes conversation over negotiation and the common good over victory. This patriotism can be global as well as local, left as well as right.